DIVERSITY OF INNOVATION TO ENHANCE CUSTOMER LOYALTY IN BATIK SLAMET HADIPRIYANTO BANYUMAS - Febrian, Feby; Zaelani Adnan, Ahmad; Setiadi Wibawa, Lutfi; Suprianto Ahmadi, Rudi; Agustina, Granit (Dinasti International Journal of Digital Business Management, 2020)
The research objective was to evaluate the relationship between innovation and customer loyalty as a determining factor in the sustainability of the marketing of batik cloth products. Design / methodology / approach - using descriptive and verification methods. The design uses consumer report data from the objective test results of 100 consumers from 3000 populations. The responses measured include innovation and loyalty. Measured data diversity and analysis was performed using simple regression to estimate customer loyalty. Findings – diversity of innovation are important factors affecting consumer loyalty of batik cloth. Research limitations/implications - understanding the patterns that lead to product innovation diversity. Practical implications – diversity of innovation with loyalty. This diversity is a way to understand and explain antecedent innovation to increase consumer loyalty to batik cloth. Originality/value development innovation diversity to increase consumer loyalty. The conclusion shows that this variable has a significant effect, namely 68.6% of the innovation variable from the loyalty, while 31.4% is explained by other variables not included in this study.